Who freezes her eggs and why? psychological predictors, reasons, and outcomes of social egg freezing - Julia Jeannine Schmid; Seraina Weber; Ulrike Ehlert (Reproductive Biology and Endocrinology)
Abstract Background Despite the growing use of social egg freezing (SEF), research focusing on its psychological aspects is lacking. This study aimed to investigate possible psychological predictors, reasons, and outcomes of SEF in German-speaking countries. Methods The cross-sectional study included 1,131 women (average age 31 years) who had never used medical egg freezing. The participants were at different stages of SEF decision-making: women who cannot imagine using SEF (SEF-non-use), women who can imagine using SEF (SEF-possible-use), women who plan to use SEF (SEF-planned-use), women who have used SEF (SEF-use), and women who have used their oocytes frozen during SEF for assisted reproduction (SEF + ART-use). Data on sociodemographic and psychological characteristics, attitudes towards motherhood, well-being, and reasons for SEF were assessed. We used multinomial logistic regression to identify predictors of SEF decision-making stages, principal components analysis to examine motives for SEF, and multiple linear regression to analyze associations between motives and psychological variables. Results The probability of belonging to the SEF-use group rather than SEF-non-use was higher among childless single women with tertiary education, high levels of employment, and high importance placed on the genetic relationship to the child, and rose with increasing age and importance of motherhood. The probability of belonging to the SEF-use group rather than SEF-planned-use was higher among childless women with a high importance placed on the genetic relationship to the child, and increased with age. The probability of belonging to the SEF + ART-use group rather than SEF-use depended mainly on the presence of infertility. The women froze eggs mainly to gain time to fulfill their desire for conventional parenthood (59%), including finding the right partner and enabling a genetic relationship to the child. Using SEF to actively shape one’s life and family planning was rather associated with positive psychological outcomes, whereas relying on SEF in the hope of personal and societal changes (e.g. improving fertility) was associated with negative outcomes. Conclusion SEF users might be characterized as mainly single, career-oriented, and greatly valuing genetic motherhood. As the motives for SEF, rather than its use per se, might be linked to psychological variables, these should be considered when counseling and supporting women.